The Impact of the COVID-19 Pandemic on Rents in the city of Seattle limits - Zhu, Jianxia (My University, 2021)
The thesis examines the extent of changes in rents during the COVID-19 pandemic at the zip code level for the city of Seattle using statistical analysis and Geographic Information Systems (GIS). The results of the study suggest there is an average decrease in rents by 6% in the study area during COVID-19 compared to 2019. Five zip codes saw a rent decline over 10% with the greatest decrease reaching 17.5%. These zip codes are located in the core of the downtown area. In terms of socioeconomic characteristics, these zip codes have high population density, high-tech employment, working-age population (18-34), and renter-occupied units rate. There is no direct correlation between the rent change and COVID-19 cases or positive rate at this level. The secondary impact of the pandemic such as work from home policy, the subsequent migration of residents, and the decline in the attractiveness of the city center are the actual reasons that affect rents.
Thesis (Master's)--University of Washington, 2021
Keywords: COVID-19; GIS; Pandemic; Rent; the city of Seattle; Zip code; Urban planning; Economics; Urban planning